Sensitivity and specificity of prior methicillin-resistant Staphylococcus aureus nasal swab results for predicting methicillin-resistant Staphylococcus aureus infections in intensive care unit admissions over a 1-year period: A pilot study - Jonathan Wadle; Geoffrey C Wall; Hayden S Smith (Wolters Kluwer Medknow Publications, 2020)
Objective: Methicillin-resistant Staphylococcus aureus (MRSA) continues to be a pathogen worldwide. Empiric anti-MRSA therapy is often prescribed in hospital inpatients with potential infection. Recent studies have suggested, particularly for respiratory infections, that MRSA colonization as determined by nasal swab has a high negative predictive value (NPV) for MRSA infections during the index hospitalization. We examined the predictive value of a prior intensive care unit (ICU) MRSA nasal swab on the results from a subsequent ICU admission in the same patient and the results of the latter admission MRSA nasal swab. Methods: A retrospective chart review of patients 18 years or older admitted to a large tertiary care hospital in the Midwest of the United States in 2016 who had a MRSA nasal swab performed and had an ICU admission stay of over 24 h was conducted. This group of patients was matched to a patient list of subjects who were admitted as an inpatient to the same ICU at least once during the following year. Data were collected on demographic and clinical information, as well as the results of MRSA swabs and the presence of a MRSA infection during both hospitalizations. Predictive values were calculated using 2 × 2 tables including sensitivity and specificity of a first MRSA swab result with a MRSA infection during the subsequent ICU stay. Findings: Seventy-seven patients were matched who had MRSA swabs performed on two separate ICU admissions. The negative predictive value of the first MRSA swab result on a MRSA infection during the second ICU stay was 96%. Conclusion: In this pilot study, a previous negative MRSA nasal swab may predict a lack of a MRSA infection in a subsequent infection during a 1-year period.